Self-concept and its relationship to the level of ambition of young handball players at Al-Kufa Sports Club - Al-Jubouri, L. Mukhlid Ni'ma Haroun (Sulaimani Journal for Humanities, 2026)
This study aimed to identify the relationship between self-concept and the level of ambition among young handball players at Al-Kufa Sports Club. It also sought to determine differences in self-concept and ambition levels among these young handball players based on variables such as club ranking, academic qualifications, playing position, experience, and place of residence. To achieve this, the study was conducted on a sample of 30 young handball players from Al-Kufa Club, randomly selected from several clubs in Najaf Governorate. The researcher employed a descriptive methodology, deemed most suitable for the nature of the study and its research questions. To measure the self-concept and ambition levels of these young handball players, the researcher developed two research instruments based on a review of educational literature related to self-concept and ambition levels in general, as well as previous studies on the topic.
Keywords: Selfconcept; level of ambition